(untitled) (Agriculture, Food, and Natural Resources Journal, 2025)
Elevation and wood specific gravity variables are used to understand forest growth and its various responses to climate. Despite this, the relationship among various forest structures, wood specific gravity, and elevation remains poorly understood. This study investigated the influence of elevation and wood specific gravity on the tree structure of a natural forest in Nnamdi Azikiwe University, Nigeria. Using a line transect, fifteen plots of 50 m x 50 m were alternately laid at 50 m intervals on three transects. Diameter at breast height (DBH, cm), tree total height (TH, m), and elevation (elev., m) were measured, while basal area (BA, m2) and wood specific gravity (WSG g/cm3) were derived. Data were analyzed using descriptive statistics and regression. Six (6) regression models were fitted and evaluated using the adjusted coefficient of determination (Adj.R2) and standard error of estimate (SEE). Results revealed that Dst had a mean and standard error of 49.0±1.80. Elevation (81.7±0.33), WSG, and BA had 0.51±0.01 and 0.14±0.01, respectively. The highest number (136) of trees was observed in the elevation class of 76-85, 86-95 had 32 trees, and <75 had the lowest (1). Elevation class (76-85) had the highest number (26) of species distribution, 86-95 had 16, and <75 had the lowest (1) number. From evaluation results, models 2 and 3 had the same and highest Adj.R2 and lowest SEE values of 0.87 and 0.08 and were selected. This study concludes that elevation and WSG influenced tree species distributions and structure. Therefore, it is recommended for further research using a larger forest area.